Cervantes' Christian Romance : A Study of Persiles y Sigismunda - Forcione, Alban K., 1938- (Book collections on Project MUSE., 1972)
Alban Forcione analyzes the problem which has most troubled modern readers of the Persiles, its episodic character and confusing proliferation of action. Examining closely the structure of the romance Cervantes considered his masterpiece and boldest contribution to literature, Mr. Forcione discerns in it a simple pattern: a coherent cycle of catastrophe and restoration linked symbolically to the Christian vision of man's fall and redemption. Originally published in 1972. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print b.